Mitigating the "Leaky Tin" Phenomenon: Developing Interactive Financial Literacy Media for Rural Elementary Students - Ulan Bidi (Journal of Education and Teaching Learning, 2025)
Low financial awareness among children can have severe negative impacts on their future economic management, as early childhood habits significantly shape adult financial character. In rural areas, financial literacy education in elementary schools remains severely neglected, often resulting in temporary and ineffective saving behaviors. This study aims to investigate the financial behavior of rural elementary students and identify effective instructional media to cultivate their financial awareness. Employing a qualitative descriptive method, data were collected through participatory observation and in-depth interviews with students and teachers at a rural elementary school in Pohuwato. The findings revealed a prevalent "leaky tin" (tabungan kaleng bocor) phenomenon, where students possess a basic instinct to save using used cans but frequently withdraw the money prematurely for short-term consumptive needs due to a lack of self-control and parental guidance. To mitigate this, theoretical instructional media are highly ineffective. The study identifies that integrating interactive-visual and applicative media—such as Creative Saving Books with visual targets, Wise Shopping Simulation Board Games, and Digital Storytelling—is urgently needed. In conclusion, synergistic efforts between schools and parents, facilitated by these interactive media, are crucial to shifting students' mindsets from merely storing money to strategically planning for the future.